134k views
1 vote
The elimination method is ideal for solving this system of equations. By which number must you multiply the second equation to eliminate the

y-varlable, and what is the solution for this system?
x+3y=42
2x-y=1

1 Answer

2 votes

Answers:

  • Triple each side of the 2nd equation
  • The solution is (x,y) = (45/7, 83/7) meaning that x = 45/7 and y = 83/7 pair up together. The fractions are reduced as much as possible.

=======================================================

Step-by-step explanation:

The 3y in the first equation must add to -3y so the y terms go away. We have -y in the second equation, which is why we triple everything in that equation

2x-y = 1 becomes 6x - 3y = 3 after tripling everything. This is the same as multiplying both sides by 3.

This is the updated equivalent system


\begin{cases}x+3y = 42\\6x-3y = 3\end{cases}

Add the terms straight down

  • x+6x becomes 7x
  • 3y+(-3y) becomes 0y or 0. The y variables are eliminated.
  • The right hand sides 42 and 3 add to 45

We have the equation 7x = 45 which solves to x = 45/7.

Unfortunately it doesn't turn into a nice single whole number because 45 isn't a multiple of 7. So I would leave it as a fraction.

Optionally you could note that 45/7 = 6.42857 approximately. But I prefer the fraction form since it's most exact.

--------------

Use this x value to find y. Pick any equation involving x and y. Plug in that x value and solve for y.

x + 3y = 42

45/7 + 3y = 42

3y = 42 - 45/7

3y = 42*(7/7) - 45/7

3y = 294/7 - 45/7

3y = (294 - 45)/7

3y = 249/7

y = (249/7)*(1/3)

y = 83/7

Like with x, we also don't get a nice whole number.

I used WolframAlpha to confirm the solutions. GeoGebra is another tool you could use.

User Crashworks
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.